Magnetic Field Induced Surface Micro-Deformation of Magnetorheological Elastomers for Roughness Control - Chen, Shiwei; Li, Rui; Li, Xi; Wang, Xiaojie (Frontiers in Materials, 2018)
We proposed a mesoscopic model to investigate the surface micro structures of magnetorheological elastomers (MREs) under a magnetic field. By comparing the surface roughness changes of MREs, we found that the surface micro-deformation of MREs, not the field-induced hardness, mainly accounts for the controllable friction characteristics of MREs. The results also demonstrate that the field-induced friction of MREs depends on the particle contents as well as the initial surface roughness. The model predicts that the maximum relative roughness change of MREs occurs at which the MRE having particle volume fraction of around 9%, which is validated by experimental results.